Histo-pathological findings in kidneys with polar artery: a demystifying endeavor - Nallagatla, N. Shakuntala; Nannam, Kavya; Kugananthan, Meera; Rao, H. R. Krishna; Kumarguru, B. N. (International Journal of Research in Medical Sciences, 2022)
Background: The kidneys are supplied by renal arteries which enter the hilum and branch progressively from the pyramids to the cortex into lobar, interlobar, arcuate, interlobar, interlobular, and finally terminate as afferent arterioles that enter the glomeruli. Thus there is a normal pattern of blood flow towards the cortex from the pyramids when the artery enters at the hilum. The aim of the study was to explore the glomeruli pattern in kidneys with polar arteries. Methods: The study was conducted in the department of anatomy at a tertiary care referral institute. Twenty-two kidneys with polar arteries were obtained by conventional method of dissection from cadavers for the study. Sections were taken from the upper pole and lower pole in each kidney. The sections were taken perpendicular and close to the polar arteries. The sections were subjected to routine histological processing and staining as per the standard operating procedure. Histological findings were observed and documented. Results: The study found that the kidneys were histologically different with polar arteries as compared to normal kidneys. The number of glomeruli per high power field was higher nearer to the polar arteries. The glomeruli were viable and not sclerosed. An agglomeration of arterioles were present close to the polar arteries but they were distinct and did not seem to be associated with glomeruli. Conclusions: The study found an agglomeration of arterioles, increased number of viable glomeruli and cystic changes associated with kidneys having polar artery. Thus this warrants a detailed study with special stains for research to elucidate the mechanisms of the circulation in polar arteries and correlation of the same findings with clinical conditions such as hypertension or any other diseases of the kidney.